Determinan Minat Masyarakat Banda Aceh Untuk Menggunakan Asuransi Syariah - Iskandar, Evy; Riza, Akmal; Putri, Indira Arsy (Jihbiz: Global Journal of Islamic Banking and Finance, 2026)
Sharia insurance can protect lives, and the insured funds can be utilized for mutual assistance among participants (tabarru’ contract). This study aims to examine the effect of financial literacy, religiosity, and trust on interest in using Sharia insurance among the community in Banda Aceh. The study employs a quantitative method with an empirical approach, and the population and sample consist of residents of Banda Aceh City. The sampling technique used is purposive sampling, with a total of 80 respondents collected through questionnaires distributed via Google Forms. Data were analyzed using multiple linear regression to test the hypotheses with the assistance of IBM Statistics software. The findings indicate that, partially, hypothesis 3 is accepted, showing that the trust variable has a significant effect on interest in Sharia insurance. Meanwhile, hypotheses 1 and 2 are rejected, indicating that financial literacy and religiosity do not have a significant effect on interest in using Sharia insurance.